تقييم بعض الطرز المحلية للبندورة.Lycopersicon esculentum Mill - معلا, محمد; سليمان, نصر; عبد الرزاق, عامر (Latakia University Journal -Biological Sciences Series, 2019)
أجريت الدراسة على اثنـي عـشـر طــرازاً وراثياً محلياً مـــن البندورة (.Lycopersicon esculentum Mill ) تم جمعها من مناطق مختلفة. تم تقييم الصفات المورفولوجية للنبات والأزهار والثمار لهذه الطرز وشملت الدراسة أيضاً أهم الصفات الاقتصادية – الغلة وعناصرها والتركيب الكيميائي للثمار على مدى موسمين متتاليين 2004 – 2005, وقد بينت النتائج وجود فروق معنوية بين هذه الطرز فيما يتعلق بمواصفات النبات والأزهار والثمار. أظهرت النتائج تفوق الطراز الرابع في طول الساق الرئيسة فكانت 370.25 سم وتفوق الطراز نفسه بمحتوى الثمار من المادة الجافة والحموضة الكلية والسكريات الكلية فكانت 6.81 %, 0.46 %, 4.09 % على التوالي. كما أظهرت النتائج أيضاً وجود ارتباط متوسط موجب بين صفة وزن الثمـرة وصـفة عــدد الحجر فـي الثمرة فـكان معامل الارتباط r = 0.40, كما لوحظ وجود ارتباط سالب بين صفة وزن الثمرة ومحتوى الثمرة من الحموضة الكلية والسكريات والمادة الجافة فكانت قيمة معامل الارتباط 0.43 - و0.19 - و0.39 - على التوالي. Twelve genotypes of local tomato (Lycopersicon esculentum Mill.) were collected from several local areas. The plant morphological characteristics, flowers and fruits were evaluated. Yield tomato genotypes and their components as well as fruits chemical contents have been studied during 2004-2005 growing seasons. Significant differences were found among these types for plant, flowers and fruits traits. Results showed that the fourth genotype had a taller main length 370.25cm and higher content of dry matter, acidity and sugar which were 6.81 %, 0.46 % and 4.09 % respectively. The result appeared also positive correlation between fruit weight and number of loculars per fruit was r = 0.40. Negative correlation between the fruit weight and fruit content of acidity and total sugar and dry matter and correlation coefficient was – 0.43, - 0.19 and – 0.39 respectively.